2020
DOI: 10.1596/1813-9450-9359
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Government in the Market for Electric Vehicles: Evidence from China

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This paper is among the first to assess the efficacy and welfare effects of tax policies that support hybrid and electric vehicles in a middle-income country, using Colombia as a case study. Several studies have examined China, which has achieved unique electric vehicle market shares, charging station networks, and domestic electric vehicle production among low and middleincome countries (Jin et al 2021;Li et al 2020;Sheldon and Dua 2020). As we show below, Colombia is a more representative middle-income economy.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This paper is among the first to assess the efficacy and welfare effects of tax policies that support hybrid and electric vehicles in a middle-income country, using Colombia as a case study. Several studies have examined China, which has achieved unique electric vehicle market shares, charging station networks, and domestic electric vehicle production among low and middleincome countries (Jin et al 2021;Li et al 2020;Sheldon and Dua 2020). As we show below, Colombia is a more representative middle-income economy.…”
Section: Introductionmentioning
confidence: 94%
“…First, as noted above, the paper is the first to evaluate electric vehicle policies in a middle-income country other than China. A growing literature examines electric vehicle demand and policy in high-income countries and China, such as Li et al (2017), Li (2019), Li et al (2020), Sheldon and Dua (2020), Xing, Leard, andLi (2021), andSpringel (2021). Colombia is unusual among these countries in using import tariffs to promote hybrid and electric vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to direct consumer subsidies, cost‐effective policies might involve government investment in charging infrastructure or providing owner benefits, for example, special license plates with parking or driving privileges (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…CYN for providing a purchase subsidy and installing public chargers respectively. 186 In addition to highlighting the evident positive correlations between the instalment of chargers and the number of EVs, some research has also answered the "chicken and egg problem" when it comes to showing whether chargers incentivise the growth of EVs markets or whether their numbers increase because of EVs becoming more and more common. 187 In that regard, studies have found that private entities are typically not willing to install chargers in ways that exceed existing demand, making it the responsibility of governments to build public chargers to stimulate initial consumer interest.…”
Section: Literature Review and Gapsmentioning
confidence: 99%